Personalized and Depersonalized Discourses: Irony and Self-Consciousness in Bécquer's Rimas - Cecile West-Settle (Studies in 20th & 21st Century Literature, 2005)
Gustavo Adolfo Bécquer's Rimas have long been read as a prelude to the later twentieth-century texts of Juan Ramón Jiménez and Jorge Guillén. This established reading of the Rimas emphasizes the romantic idealism of Bécquer's poetry and identifies Bécquer as a proto-symbolist poet whose work anticipates "pure" poetry in Spain. An alternate view of the Rimas, one that recognizes the ironic impulses of this poetry, reminds us that Bécquer's poetry and poetics are, rather than single-minded, grounded in paradox and concerned with one of art's central problems, that is to say, with representing what the limitless imagination produces within the limits of language.
Keywords: Gustavo Adolfo Bécquer; rimas; Juan Ramón Jiménez; Jorge Guillén; irony; poetry; paradox; paradoxical; limits; imagination